Autoerotic asphyxia using a plastic bag loosely covering the head over a gas mask. (May 2019) - Idota, Nozomi; Nakamura, Mami; Tsuboi, Hajime; Ichioka, Hiroaki; Shintani-Ishida, Kaori; Ikegaya, Hiroshi
Highlights: The death of a 33-year-old man was a suspected case of autoerotic death (AED). He wore a gas mask and plastic bag: an atypical method for autoerotic play. The features of AED in eight Japanese cases are similar to those in the West. The police investigation is very important for determining the manner of death. During an autopsy, we should keep in mind any evidence that would rule out AED. Abstract: Autoerotic death is defined as the accidental death of an individual while masturbating, caused by a device or material used to enhance the sexual response. Here we report an autopsy case of autoerotic death and review the literature. A healthy, single, 33-year-old Japanese male was found dead in his room in a prone position. He was wearing a used gas mask and a plastic bag over his head; the opening of that bag was loosely secured around the neck with a belt. He had no underwear beneath his upper and lower work clothes and the zipper of his pants was open. Adult magazines and DVDs featuring male subjects and other adult toys were found in his room. Images of people wearing gas masks and rubber suits, as well as of individuals whose whole bodies were tied with ropes, were discovered on his personal computer. Records of purchasing full-body tights were also found. Lesions and injuries that could have caused his death were not found in the autopsy or in any of the various examinations. The cause of death was determined to be suffocation assumed to be caused by the plastic bag covering the mask's ventilation. Suicide and homicide were ruled out based on the police investigation of the scene of the victim's death and the attendant circumstances and environment. The death was thus determined to be an accident. We see no major differences in the feature of autoerotic death between Japanese cases and those in the Western countries.